Management Of Eales’ Disease Grade III B: A Rare Case - Evasha, Agung Putra; Amin, Ramzi; Ansyori, A.K. (Indonesian Vitreoretinal Society, 2023)
Introduction: Eales' disease is an idiopathic, bilateral, occlusive retinal vasculopathy that primarily affects young, predominately male patients. It seems to have multiple causes and is probably immunologic in nature. Recurrent vitreous hemorrhages, macular degeneration, and tractional or mixed retinal detachments involving the macula can all cause some patients to experience severe vision loss. Case Report: A 39-year-old male with vitreous hemorrhage caused by Eales Disease grade III Bwith an initial visual acuity 1/300 came to our department. Ultrasound imaging showed themembrane like lesion with 1/2 retinal reflectivity, after moderate movement and vitreoushemorrhage on both eyes. The photo-fundus showed there is decreased fovea reflex andperimacular exudate with visible contours of sclerotic blood vessels, visible cotton wall spot, andmacroaneurysm. There is also haze grade 3 on media, visible folds in the inferior part, visibleshadows of cotton wall spots. The patient underwent pars plana vitrectomy with endolaser tomanage the disease. Discussion: In this case, patient was diagnosed as vitreous hemorrhage caused by Eales Diseasegrade III B on both eyes but it getting worse on left eye further. We chose to perform PPV withendolaser on right eye. Based on improved visual acuity and less hemorrhage, the right eye'soutcome was favorable, while the left eye, which was not treated, had a worsening of thesituation. Only eyes with a non-resolving vitreous hemorrhage after three months should have avitrectomy.Conclusion: The treatment of this patient's case produced good anatomical and functionaloutcomes for the right eye, but the left eye, unfortunately, has a major issue. In order to furtherconfirm the results, longer follow-up is still required.